TRACING INFORMATION LITERACY OF COMPUTER SCIENCE UNDERGRADUATES: A CONTENT ANALYSIS OF STUDENTS’ ACADEMIC EXERCISE - N.N., Edzan (Malaysian Journal of Library and Information Science, 2017)
Librarians have been using citation analysis as a means to determine the usage of their collection while others have used it look at undergraduate information behaviour. At the same time, various attempts are being made to relate citation analysis of bibliographies to information literacy competencies by mapping them to the performance indicators of established information literacy standards. This paper describes the analysis of bibliographies of final year project reports emanating from the Faculty of Computer Science and Information Technology, University of Malaya. A total of 73 reports were analysed using a pre-designed scoring sheet and results presented included number of pages, number of citations, types of sources used, usage of Web resources, currency of sources and citation style. The contents analysis of the bibliographies indicates: (a) the least number of citations per report is 6 and the most is 165 with the most number of citations within the range of 11 to 20 cites; (b) there are more Web citations than citations to books, journal articles, undergraduate reports, Masters’ dissertations and conference papers; (c) there are more citation to .com than to .org, .edu, .net and other URL extensions; (d) most citations are not dated and most of those dated are from within the last three years with the most current being 2005 and the oldest dated citation is 1935; and (e) most references have their print citations cited correctly but the Web citations cited incorrectly. Only a handful of indicators could be matched to the information literacy performance indicators of the ALA/ACRL/STS 2005 Information Literacy Standards for Science and Engineering/Technology